1996
DOI: 10.1046/j.1365-2958.1996.281397.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the mexC–mexD–oprJ efflux operon in nfxB‐type multidrug‐resistant strains of Pseudomonas aeruginosa

Abstract: OprJ, overproduced in nfxB multidrug-resistant strains of Pseudomonas aeruginosa, and OprK, overproduced in the multidrug-resistant strain K385, were demonstrated to be immunologically cross-reactive using an OprJ-specific monoclonal antibody. Treatment of the purified proteins with trypsin or chymotrypsin yielded virtually indistinguishable digestion patterns, and the N-terminal sequence of two trypsin fragments was identical for both proteins, indicating that OprJ and OprK share identity. The N-terminal amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
377
1
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(392 citation statements)
references
References 40 publications
9
377
1
5
Order By: Relevance
“…In several clinically isolated mutants of P. aeruginosa, higher expression of RND-type efflux pumps was observed (Hirai et al, 1987;Rella & Haas, 1982;Wolter et al, 2004). Of the 11 RND efflux pumps identified in this organism, 10 pumps, MexAB-OprM (Poole et al, 1993), MexCD-OprJ (Poole et al, 1996), MexEF-OprN (Kohler et al, 1997), MexGHI-OpmD (Aendekerk et al, 2002;Sekiya et al, 2003), MexJK (Chuanchuen et al, 2002), MexMN (Mima et al, 2005), MexPQ-OpmE (Mima et al, 2005), MexVW (Li et al, 2003), MexXY (Mine et al, 1999;Westbrock-Wadman et al, 1999) and TriABCOpmH (Mima et al, 2007), have been experimentally confirmed, and their properties have been reported. The RND-type efflux pump usually consists of three components to fulfil the function properly and includes an innermembrane component (RND component), a periplasmic component (MFP component), and an outer-membrane component (OMP component) (Touze et al, 2004), and the three-dimensional structures of MexA, MexB and OprM have been reported (Akama et al, 2004a, b;Higgins et al, 2004;Sennhauser et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…In several clinically isolated mutants of P. aeruginosa, higher expression of RND-type efflux pumps was observed (Hirai et al, 1987;Rella & Haas, 1982;Wolter et al, 2004). Of the 11 RND efflux pumps identified in this organism, 10 pumps, MexAB-OprM (Poole et al, 1993), MexCD-OprJ (Poole et al, 1996), MexEF-OprN (Kohler et al, 1997), MexGHI-OpmD (Aendekerk et al, 2002;Sekiya et al, 2003), MexJK (Chuanchuen et al, 2002), MexMN (Mima et al, 2005), MexPQ-OpmE (Mima et al, 2005), MexVW (Li et al, 2003), MexXY (Mine et al, 1999;Westbrock-Wadman et al, 1999) and TriABCOpmH (Mima et al, 2007), have been experimentally confirmed, and their properties have been reported. The RND-type efflux pump usually consists of three components to fulfil the function properly and includes an innermembrane component (RND component), a periplasmic component (MFP component), and an outer-membrane component (OMP component) (Touze et al, 2004), and the three-dimensional structures of MexA, MexB and OprM have been reported (Akama et al, 2004a, b;Higgins et al, 2004;Sennhauser et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…In Pseudomonas aeruginosa, resistance to a variety of antimicrobial agents is conferred by the synergy between low permeability of the outer membrane and several RND multidrug efflux systems, of which MexAB-OprM (Poole, 1993;Li et al, 1994Li et al, , 1995b and MexCD-OprJ (Masuda et al, 1995, Poole et al, 1996 contribute to the resistance to tetracycline. They both consist of three components: MexA or MexC (periplasmic MFP proteins), MexB or MexD (inner membrane RND proteins) and OprM or OprJ (outer membrane channel proteins) and they pump drugs from the cytoplasm into the medium.…”
Section: Multidrug Transportersmentioning
confidence: 99%
“…MexC associates with the inner membrane transporter MexD and the outer membrane ef¯ux protein OprJ to form a multidrug export complex, which is overexpressed in strains resistant to chloramphenicol, erythromycin, tetracycline, quinolones, and cefpirom (Miche Âa-Hamzehpour et al, 1995;Poole et al, 1996). The MexC peptides, residues 64-95 and 172-208, completely span the conserved motif (Figure 2).…”
Section: Circular Dichroism Spectroscopy Of Pep Peptidesmentioning
confidence: 99%